Effectiveness of Higher Order Thinking Skills-based Test Instruments in Science Learning in Indonesia: A Meta-analysis - Tomi Apra Santosa; Siska Angreni; Rona Taula Sari; Festiyed; Yerimadesi; Yuni Ahda; Heffi Alberida; Fitri Arsih (Jurnal Penelitian Pendidikan IPA, 2024)
This research is motivated by the many applications of Higher Order Thinking Skills-based test instruments in science learning. However, it has not been found how effective the instrument is in science learning. The purpose of this study was to determine the effectiveness of Higher Order Thinking Skills-based test instruments in science learning. This type of research is a meta-analysis. Data sources come from the databases of Google Scholar, Hindawi, ScienceDirect, Wiley, Taylor of Francis, Sage Journal, Springer, ProQuest and ERIC. Search keywords are test instruments, test instruments based on Higher Order Thinking Skills in science learning, and higher order thinking skills. This study analyzed 20 articles published in 2020-2023 used in the meta-analysis. Data analysis techniques with the help of JSAP software. The results concluded that the summary effect size value was 1.24 (very high effect size). This finding shows that the use of test instruments based on Higher Order Thinking Skills is effectively applied in science learning. Furthermore, the research provides higher order tinking skills-based test instruments in science learning in Indonesia and provides important information for the application of higher order thinking skills-based test instruments in the future